PERTUKARAN SOSIAL DALAM PROSES TA'ARUF ONLINE: Studi Kualitatif Terhadap Anggota Yayasan Rumahati Dalam Perkembangan Teknologi 4.0 - Muhammad Reza Akbar (2020)
This study discusses social exchange in the online taaruf process. Taaruf Online is a syar`i media that can be used to introduce potential partners. The part that is used as an introduction is not only related to available data, but also explains information that according to each party is quite important, for example the physical problems of the prospective wife, is allowed to look directly at his face in a careful manner, and to avoid stealing the candidates' eyes. the members of ta'aruf. This research uses social exchange theory. The purpose of this research is to find out whether or not there is social exchange in online ta'aruf. This study used descriptive qualitative method. In this research, the case study used is a prospective partner of the taatif online foundation of Rumahati who conducts taaruf online. The research data was obtained through an online interview with the prospective partner of the taati ta online house of foundation. The results of this study stated that social exchange in taaruf online affects prospective couples online taatiuf foundation rumahati in choosing prospective partners with the aim of getting a life partner and having a marriage.